BODY POSITION (POSTURE), MOVEMENTS OF SOME JOINTS, THE PATH (TRAJECTORY) OF PHYSICAL EDUCATION OF CHILDREN OF DIFFERENT AGES, CONTENT AND METHODS OF ITS ORGANIZATION - Uraimov Sanjar Rozmatovich; Abdurakhimova Hayotkhan (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article presents information on the body condition of students of different ages and some of their joints, the initial condition and changes in the organism.